PENGARUH BRAND AMBASSADOR, BRAND IMAGE, BRAND TRUST TERHADAP MINAT BELI: SEPATU SPECS - Dispar, Kevin Arigi; Anggarawati, Sularsih (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This article aims to examine the influence of brand ambassador, brand image and brand trust on purchase intention. As many as 238 respondents used non-probability techniques in purposive sampling as a sampling technique. This research uses regression analysis tools. The research results show that brand ambassador does not have a significant influence on purchase intention, brand image has a significant influence on purchase intention, then brand trust also has a significant influence on purchase intention in purchasing SPECS sports shoes.